Avaliação e quantificação dos componentes do balanço hídrico em pomar de pessegueiro, cv. Maciel, em plantas irrigadas e não irrigadas. - Terra, Viviane Santos Silva (2010)
The South region of Brazil (Pelotas, state of Rio Grande do Sul) is responsible for the production of temperate fruit trees. Among them, the peach crop has been a good option for crops diversification. The knowledge of the amount of available soil water to supply water needs during the peach different stages of development is of interest to the agronomic point of view. In this sense, we highlight the importance of the use of irrigation in peach orchards in order to provide an adequate crop water supply. It is therefore important to know the response of peach to water deficit so that we can assess the influence of the practice of irrigation in crop production. Among the methodologies, the soil water balance, which consists of applying the equation of conservation of mass, has been used. Based on this, the main objective of this work was to evaluate and quantify the different components of water balance in a Red Yellow Podzolic soil, planted with peach trees, cultivar Maciel, under irrigation and without irrigation and to verify the adequacy of Domain Reflectometry Frequency (FDR) equipment for monitoring the water content over time. The evaluation and quantification of different components of water balance of soil water were measured in an experimental area which belongs to Embrapa Clima Temperado, Pelotas-RS, Brazil, planted with peach cultivar Maciel, nearby plants irrigated and not irrigated. For this, the water balance calculation was carried out weekly and divided into 32 periods, of which 4 periods (12, 20, 24 and 26) were discarded because they had precipitation above 30 mm week-1. The experimental area containing irrigated and no irrigated plants was divided into five strips. The irrigated plants belonged to the strip 1 (tubes 3 and 6), strip 2 (tube 2) and strip 3 (tube 1), each one with an area of 0.5 m². The no-irrigated area belonged to the strip 4 (tube 8) and 5 (tube 7), with an area of 1 meters each one. Strips 1, 2 and 4 were under canopy and the other outside of the canopy. Rainfall was measured by rain gauges; irrigation water supply was made based on the average daily evapotranspiration of the region; the variation of water storage in the soil was measured by readings of soil water content up to 0.50 m depth, using an equipment based on reflectometry in the frequency domain (FDR) which was calibrated from readings of tensiometers; the runoff and internal drainage or capillary rise were neglected; and the actual evapotranspiration (ETr) was taken as the unknown variable. From the results we can conclude that it is possible to use an indirect method, using tensiometers and soil water retention curves to obtain calibration curves of the reflectometry equipment in the frequency domain (FDR); the adopted irrigation management, based on the average evapotranspiration of the region, may not be sufficient to supply the water requirements of peach crop; peach trees with water supply through irrigation have higher values of actual evapotranspiration; and soil water storage ranged in all irrigated and no irrigated strips between 60 and 140 mm week-1, unaffected by the adopted treatments in the study.